Specific Antibody Levels and Antigenic Recognition of Wistar Rats Inoculated with Distinct Isolates of Trypanosoma evansi - Queiroz, Adriana O. (2001)
Fundação Oswaldo Cruz. Instituto Oswaldo Cruz. Departamento de Protozoologia; Rio de Janeiro, RJ, Brasil.